Pembelajaran Daring Masa Pandemi (Studi Kasus Kegiatan Belajar di Rumah Dalam Group Kelas IV MI As Salam) - Nur Samsiyah (IBTIDA', 2020)
Online learning was carried out by teachers during the pandemic, one of which was at Madrasah Ibtidayah. This study aims to determine the learning activities and material taught at MI As-Salam in Madiun district during the learning period at home. The data were collected by observing, interviewing and documenting in the fourth grade group, totaling 30 students. Based on the analysis of the data from the case study results, it can be concluded that thematic learning is in a poor category because the activities carried out by students are more work on assignments, while other subjects such as PJOK have quite good activities because they are done in practice and use learning media in providing material. Learning with assignments is influenced by the unpreparedness of the teacher in providing learning tools and the teacher's target of completing learning in the theme according to time, so that learning activities are not optimal.